Chimeric NUP98–NSD1 transcripts from the cryptic t(5;11)(q35.2;p15.4) in adult de novo acute myeloid leukemia. Issue 3 (4th March 2018) - Kivioja, Jarno L.; Lopez Martí, Jesus M.; Kumar, Ashwini; Kontro, Mika; Edgren, Henrik; Parsons, Alun; Lundán, Tuija; Wolf, Maija; Porkka, Kimmo; Heckman, Caroline A.
Abstract: The t(5;11)(q35;p15.4) is a clinically significant marker of poor prognosis in acute myeloid leukemia (AML), which is difficult to detect due to sub-telomeric localization of the breakpoints. To facilitate the detection of this rearrangement, we studied NUP98–NSD1 transcript variants in patients with the t(5;11) using paired-end RNA sequencing and standard molecular biology techniques. We discovered three NUP98–NSD1 transcripts with two fusion junctions ( NUP98 exon 11-12/ NSD1 exon 6), alternative 5′ donor site in NUP98 exon 7, and NSD1 exon 7 skipping. Two of the transcripts were in-frame and occurred in all t(5;11) samples ( N = 5). The exonic splicing events were present in all samples ( N = 23) regardless of the NUP98–NSD1 suggesting that these novel splice events are unassociated with t(5;11). In conclusion, we provide evidence of two different NUP98 – NSD1 fusion transcripts in adult AML, which result in functional proteins and represent suitable molecular entities for monitoring t(5;11) AML patients.